2006
DOI: 10.1191/0748233706th244oa
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of subchronic exposure to diesel-water-methanol emulsion emission

Abstract: The U.S. Environmental Protection Agency's National Ambient Air Quality Standards for ozone and particulate matter (PM) require urban non-attainment areas to implement pollution-reduction strategies for anthropogenic source emissions. The type of fuel shown to decrease combustion emissions components versus traditional diesel fuel, is the diesel emulsion. The Lubrizol Corporation, in conjunction with Lovelace Respiratory Research Institute and several subcontracting laboratories, recently conducted a health as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
2
15
0
1
Order By: Relevance
“…Because of this, SOA has rarely been considered by health scientists who, in large part, have focused research efforts on concentrated ambient particles (that contain SOA in part), diesel exhaust (EPA, 2002), sulfate (Schlesinger, 2007), and to a lesser extent, gasoline engine emissions and wood smoke (Reed et al, 2006). SOA is also difficult to study directly.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, SOA has rarely been considered by health scientists who, in large part, have focused research efforts on concentrated ambient particles (that contain SOA in part), diesel exhaust (EPA, 2002), sulfate (Schlesinger, 2007), and to a lesser extent, gasoline engine emissions and wood smoke (Reed et al, 2006). SOA is also difficult to study directly.…”
Section: Research Articlementioning
confidence: 99%
“…EPA, 2002;McDonald et al, 2007), wood smoke (e.g. Reed et al, 2006) and inorganic ions such as sulfate (Reiss et al, 2007;Schlesinger, 2007). The epidemiological literature is scant on this subject, although a recent study revealed a stronger association between daily mortality and fine particulate air pollution in summer than in winter, suggesting that SOA may substantially contribute to the observed effect on mortality owing to high PM levels in summer being typically associated with the production of SOA (Nawrot et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…NO and PM were reduced when engines were operated on Puri NO x versus California Air Resources Board diesel fuel under these conditions. 18 In a different study, 19 a stabilized methanol-diesel blend was developed and combustion characteristics and heat release analysis were carried out in a CI engine. According to the experimental results, increasing the methanol mass fraction in the methanol-diesel fuel blends resulted in an increase in the heat release rate at the premixed burning phase and shortened the combustion duration at the diffusive burning phase.…”
Section: Introductionmentioning
confidence: 99%
“…The investigators concluded that "comparisons of the biological responses to these two fresh combustion emissions at levels relevant to potential human exposure levels suggest relatively little overt toxicity" . Corroborating these findings are several recent subchronic inhalation studies of alternative diesel fuels, also conducted at Lovelace Respiratory Research Institute, that have similarly reported evidence of only mild health effects for diesel-water-methanol emulsions (Reed et al, 2005(Reed et al, , 2006 and soybean oil-derived biodiesel fuel (Finch et al, 2002).…”
Section: Subchronic and Chronic Effectsmentioning
confidence: 85%